Ambulatory blood pressure, proteinuria and uric acid in children with IgA nephropathy and their correlation with histopathological findings - Seeman, Tomás; Pohl, Michael; John, Ulrike; Dusek, Jirí; Vondrák, Karel; Janda, Jan; Stejskal, Josef; Groene, Hermann-Josef; Misselwitz, Joachim (Kidney & blood pressure research, 2008)
BACKGROUND/AIMS: In adults, nighttime hypertension and hyperuricemia are new risk factors for progression of IgA nephropathy (IgAN). In children, nighttime blood pressure (BP) and serum uric acid have never been investigated. The aim of the study was to investigate nighttime BP and uric acid in children with IgAN. METHODS: Data on children with IgAN from two pediatric nephrology centers were retrospectively reviewed (renal biopsy - subclasses according Hass I-V, ambulatory blood pressure monitoring ABPM, serum uric acid, proteinuria). RESULTS: Twenty-eight untreated children with IgAN were included. Hypertension was diagnosed on the basis of ABPM in 54% of children, 50% were nondippers and 25% have isolated nighttime hypertension. The mean ambulatory BP was higher at nighttime than during daytime (systolic nighttime BP 1.11 +/- 0.79 SDS vs. daytime 0.59 +/- 0.79, diastolic nighttime BP 1.16 +/- 0.95 vs. daytime 0.52 +/- 1.10, p < 0.01 for systolic and p = 0.01 for diastolic). Children with severe histological subclasses (III-IV) tended to have higher prevalence of hypertension than children with mild subclasses (I-II), 67% vs. 38%, p = 0.13. Hyperuricemia was diagnosed in 14% of children. A significant correlation was found between proteinuria and histopathological subclasses (r = 0.44, p < 0.05). CONCLUSION: Children with IgAN have often nighttime hypertension. Hypertension and proteinuria are associated with severe histopathological findings. Hyperuricemia is a rare finding in children.
Keywords: Male; Proteinuria; Glomerulonephritis, IGA; IgA nefropatie; retrospektivní studie; proteinurie; Diastole; Uric Acid; diastola; hyperurikemie; Humans; kyselina močová; cirkadiánní rytmus; systola; mužské pohlaví; Female; mladiství; Hyperuricemia; ženské pohlaví; Retrospective Studies; Circadian Rhythm; Adolescent; lidé; dítě; Systole; Blood Pressure Monitoring, Ambulatory; Child; ambulantní monitorování krevního tlaku